A vulnerable soil environment study in karst areas: a bibliometric analysis - Yan, Taotao; Xue, Jianhui (Frontiers in Environmental Science, 2024)
Karst landforms are widely distributed around the world, and karst rocky desertification has occurred on a large scale in many countries and regions, causing significant adverse impacts on local natural environments and societies. The improvement and rational use of karst soil is a key aspect of rocky desertification governance. Karst soil science studies are of great value in karst regions and are essential for controlling karst rocky desertification and ecological restoration. In order to understand the research hotspots and the development directions in the field of vulnerable karst soil environment, we undertook bibliometrics citation analysis on 1913 contributions to the literature written in the range from 2001 to 2019 based on the "Web of Science" core collection citation index database. Hopefully, this work will help to set up a scientific foundation for further studies. In this study, a bibliometric review of the Web of Science core collection of the field of karst soil science was conducted. The annual number of articles published in the literature between 2001-2019 was evaluated. Then, uUsing CiteSpace visualization software, we analyzed the distribution of disciplinary categories, reference co-citation clusters, and keyword clusters in the literature. The results show the basic characteristics and evolution of the literature related to karst pedology. We then recognized the main intellectual bases in the domain of karst soil science. This study also revealed the research hotspots and trends in this field. Through a bibliometrics citation analysis n in-depth analysis of research on karst vulnerable soil environment soil research, the present study provides a quantitative and objective understanding of development directionsdevelopment trends that have emerged in this field over the past 19 years, offering a reference for future research.